(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: The generation of the waste and collection, processing, transport and disposal of waste -the process of ‘waste management’ - is important for both health’s of the public and aesthetic and environmental reasons. The study uncontrolled hazards waste from the industry after mixing with municipal waste create potential risk to human health. Objectives: 1. To assess the knowledge and practice regarding household waste management among the rural community 2. To Assess Effectiveness of Planned Teaching on Knowledge and Practice Regarding Household Waste Management among the Rural Community People in Selected Area of Wardha District. 3. To correlate the study finding with demographic variable. Materials and Methods: This study was based on one group pre-test post-test experimental research study. The population was the rural community people from Sawangi and Salod in the Wardha district. The subject consisted of 50 community people of 18-50 years of age in the selected rural community of Wardha district. Results: The minimum score in the posttest was 13 and the maximum score was 18, the mean score for the posttest was 16.04±1.10 with a mean percentage score of 89.11±6.14. The tabulated value for n=50-1 i.e. 49 degrees of freedom was 2.00. The calculated ‘t’ value is much higher than the tabulated value at 5% level of significance for overall knowledge score of community people which is a statistically acceptable level of significance.